Practice-Oriented Direction of Professional Preparation of Future Teachers of Primary Education in the Context of European Integration Processes - Koval, Liudmyla; Popova, Olga; Nikonenko, Tetyana (Journal of History Culture and Art Research, 2019)
The article reveals the essence of practice-oriented training of future teachers of primary education on the basis of the implementation of contextual learning technology. An express analysis of the phenomenon of pedagogical thinking was made, certifying that it personifies the level of development of mental, cognitive, creative, and research abilities of the future teacher of primary education, his operational and technological skills, which consist in finding solutions to any problem situation; in shaping pedagogical thinking of future teachers of primary education a special role was played by pedagogical situations that were solved with the help of practice-oriented tasks (pedagogical tasks). In the process of experimental learning, we specifically modeled pedagogical situations that were solved using a system of practice-oriented tasks represented by three groups: general pedagogical, didactic-methodical, and reflexive-design. No less important for the development of pedagogical thinking of future teachers of primary education during practical and laboratory classes was the use of interactive teaching methods, namely: brainstorming, discussion, debate, various types of training, etc. The active introduction of contextual learning technology, based on the practice-oriented activity of teachers, first of all, influenced the formation of a new pedagogical thinking and provided for an understanding of the value-attitude to the future profession, and an awareness of one’s own capabilities that determine professional growth paths.